Integrating comprehensive geriatric assessment into routine nursing care for older adults with type 2 diabetes: implementation fidelity and clinical outcomes - Sun, Qinqin; Ren, Dongmei; Tong, Jianping; Ao, Li; Wang, Shaowen (Frontiers in Public Health, 2025)
BackgroundComprehensive geriatric assessment (CGA) offers promise for improving diabetes management in older adults; however, its real-world effectiveness depends on implementation fidelity, which remains poorly understood. This study examined fidelity variations and their associations with clinical outcomes in nurse-led CGA for older adults with type 2 diabetes at a tertiary care hospital in China.MethodsThis cross-sectional implementation study enrolled 3,351 adults aged ≥65 years with type 2 diabetes from Shanghai Jiading District Central Hospital between March 2021 and February 2025. Implementation fidelity was assessed using five validated dimensions yielding a composite score (mean 0.64, SD 0.19; range 0.28–0.94). Primary outcome was glycated hemoglobin (HbA1c); secondary outcomes included cardiometabolic parameters, patient-centered measures, healthcare utilization, and hypoglycemic events. Linear regression models with robust standard errors adjusted for confounders; mediation analysis examined functional status pathways.ResultsFidelity demonstrated variation within the hospital (mean 0.64, SD 0.19; range 0.28–0.94), with higher educational attainment, provider experience, and CGA training completion associated with better implementation quality. Higher fidelity was associated with lower HbA1c (adjusted β −0.38 per 0.10-unit increase, 95% CI −0.47 to −0.29; p < 0.001), with a graded association across quartiles [7.89% (95% CI 7.78–8.00) in the lowest quartile vs. 7.16% (95% CI 7.04–7.28) in the highest quartile; p for trend < 0.001]. Benefits were associated with lower systolic blood pressure (−5.10 mm Hg, 95% CI −7.20 to −3.00), LDL cholesterol (−6.50 mg/dl, 95% CI −9.10 to −3.90), improved quality of life (EuroQol-5D: 0.061, 95% CI 0.041–0.081), and decreased depressive symptoms (−1.10, 95% CI −1.40 to −0.80; all p < 0.001). Healthcare utilization declined (hospitalization incidence rate ratio 0.61, 95% CI 0.51–0.73; p < 0.001), and odds of hypoglycemic events were lower (odds ratio 0.78, 95% CI 0.72–0.84; p < 0.001). Functional status was an estimated mediator of 31.6% of the fidelity–HbA1c association (indirect β −0.12, 95% CI −0.17 to −0.07; p < 0.001), with age and gait speed modifying associations (p = 0.04 and 0.02, respectively).ConclusionHigh-fidelity CGA integration is associated with substantial clinical benefits and lower healthcare utilization; while suggestive of economic advantages, a formal cost-effectiveness evaluation was not undertaken. These associations support an institutional focus on provider training, experience development, and patient education to optimize geriatric diabetes care quality.